U-Pb geochronology and paleogeography of the Valanginian–Hauterivian Neuquén Basin: Implications for Gondwana-scale source areas - Schwarz, Ernesto; Finzel, E.S.; Veiga, Gonzalo Diego; Rapela, Carlos Washington; Echevarria, C.; Spalletti, Luis Antonio (Geosphere)
Sedimentary basins located at the margins of continents act as the final base level for continental-scale catchments that are sometimes located thousands of kilometers away from the basin, and this condition of exceptionally long sediment transfer zones is probably reinforced in supercontinents, such as Gondwana. One of the most prominent marine basins in southwestern Gondwana during the Jurassic and Early Cretaceous was the Neuquén Basin (west-central Argentina), but its role as a sediment repository of far-flung source areas has not been extensively considered. This contribution provides the first detailed detrital-zircon U-Pb geochronology of the Valanginian–Hauterivian Pilmatué Member of the Agrio Formation, which is combined with sedimentology and paleogeographic reconstructions of the unit within the Neuquén Basin for a better understanding of the fluvial delivery systems. Our detrital-zircon signatures suggest that Triassic–Permian zircon populations were probably sourced from the adjacent western sector of the North Patagonian Massif, whereas Early Jurassic, Cambrian, Ordovician, and Proterozoic grains were most likely derived from farther east, in the eastern sector of the North Patagonian Massif, as well as presently remote terranes such as the Saldania Belt in southern Africa. We thus propose a Valanginian–Hauterivian longitudinal delivery system that, starting in the mid-continent region of southwestern Gondwana and by effective sorting, was bringing fine-grained or finer caliber sand to the Neuquén Basin shoreline. This delivery system was probably active (though not necessarily continuously) from Early Jurassic to Early Cretaceous until finally coming to an end during the opening of the South Atlantic Ocean in the latest Early Cretaceous. Fil: Schwarz, Ernesto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigaciones Geológicas. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de ...